2016
DOI: 10.1017/s0007114516000799
|View full text |Cite
|
Sign up to set email alerts
|

High variation in manufacturer-declared serving size of packaged discretionary foods in Australia

Abstract: Despite the potential of declared serving size to encourage appropriate portion size consumption, most countries including Australia have not developed clear reference guidelines for serving size. The present study evaluated variability in manufacturer-declared serving size of discretionary food and beverage products in Australia, and how declared serving size compared with the 2013 Australian Dietary Guideline (ADG) standard serve (600 kJ). Serving sizes were obtained from the Nutrition Information Panel for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Research suggests that a lack of serving size standardization among similar foods may affect the objectives of nutrition labeling, as it complicates food choices 6,[13][14][15] . Studies have suggested that this lack of serving size standardization may be related to the energy density of processed foods 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that a lack of serving size standardization among similar foods may affect the objectives of nutrition labeling, as it complicates food choices 6,[13][14][15] . Studies have suggested that this lack of serving size standardization may be related to the energy density of processed foods 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Classification of packaged foods as healthy and unhealthy was reported . Nutrient profiling models utilized included the Food Standards Australia New Zealand (FSANZ) Nutrient Profiling Scoring criterion, which is used to determine whether a food is suitable to make a health claim ; the New South Wales School Canteen criteria, criteria developed for an Australian food company, and the United Kingdom Traffic Light criteria ; the Health Star Rating front‐of‐pack labelling device scores ; and the Australian Dietary Guidelines . Changes in energy, total fat and protein content of yogurts and dairy desserts were assessed over time .…”
Section: Resultsmentioning
confidence: 99%
“…Classification of packaged foods as healthy and unhealthy was reported (28,54,57,67,68 Use of promotional signage to identify nutritious foods (83,94) 2 Prevalence of unhealthy foods in store external displays (86) 1 Impact of supermarket health promotion interventions (95,96,109) 3…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…Targeting the serving sizes of discretionary foods, especially those that are consumed in large quantities, is one strategy that can help to reduce excessive energy intake . However, there is currently little information available to guide consumers towards choosing appropriate portion sizes, with serving sizes being at the discretion of the supplier, and are not standardised within product categories . In addition, the vast variety of products included within the discretionary foods category limits clear guidelines for discretionary serving sizes.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, there is currently little information available to guide consumers towards choosing appropriate portion sizes, with serving sizes being at the discretion of the supplier, and are not standardised within product categories. 7,8 In addition, the vast variety of products included within the discretionary foods category limits clear guidelines for discretionary serving sizes. As food serving sizes are often used as a cue to guide an individual on how much to eat, 9 it is important to formulate feasible and standard quantities for consumption, which align with Australian Dietary Guidelines advice on discretionary foods.…”
Section: Introductionmentioning
confidence: 99%